Numerical investigation of unsteady pressure pulsation characteristics in an ultra-low specific-speed centrifugal pump as a turbine - Yangyang Wei; Yuhui Shi; Qing Zhang; Weidong Shi (Frontiers in Energy Research, 2023)
The unsteady flow characteristics of pump as hydraulic turbine play a vital role in its safe and stable operation, while the ultra-low specific-speed centrifugal pump may face more stability problems due to the limitations of its flow conditions under the turbine working condition. Therefore, in this study, the unsteady characteristics of an ultra-low specific-speed centrifugal pump under turbine conditions are studied using a numerical simulation method, and the numerical simulation is verified using an experimental method. Based on the hydraulic losses of each flow passage component, the energy characteristics of pump as turbine (PAT) are established, and the distribution pattern of total pressure fluctuation in the turbine is studied. The results show that the rotor–stator interaction between the impeller and the tongue makes the hydraulic performance and the internal flow field change periodically. The pressure fluctuation intensities at the tongue, blade inlet edge, and balance hole are large, and the total pressure fluctuation in the three areas is intense in space and time. The internal flow characteristics at typical blade positions show that the secondary flow phenomena such as separation flow and wake flow near the tongue make the pressure gradient larger, which is an important influence mode of the rotor–stator interaction. This study provides a reference and guidance for the unsteady study of low specific-speed PAT.